Vocational Identity in Social Work: A Co-occurrence Analysis of Scientific Trends - Cădariu, Ioana-Eva; Rad, Dana (Technium Social Sciences Journal, 2025)
This paper gives a bibliometric overview of the science literature examining the intersection of vocational identity and social work according to the Web of Science Core Collection. By means of co-occurrence analysis of all the keywords on VOSviewer and full counting procedures, the paper identified 182 applicable terms which fell into four general thematic clusters. These clusters—identity and career development, social justice and empowerment, vocational rehabilitation and systemic barriers, and professionalism in practice—reveal a multidisciplinary landscape shaped by psychological, educational, and structural influences. The overlay visualization reveals temporal patterns of publication with growing interest in constructs such as career adaptability, resilience, and work volition. The study sheds light on relational, developmental, and sociocultural dimensions of vocational identity within stigmatized, marginalized, or constrained institutional contexts. The work emphasizes psychological salience concerning self-efficacy, agency, and meaning-making in the context of career development, coupled with gaps involving trauma, intersectionality, and non-Western representation. This study contributes to a more comprehensive theory of vocational identity as a personal and socially embedded construct, with implications for social work, psychology research, practice, and policy.